Blood Flow and Thrombosis - Goldsmith, Harry L. (Thrombosis and Haemostasis, 1974)
Platelet thrombi have been observed at bifurcations, constrictions and stenoses in the arterial tree where flow separation with accompanying vortex formation can occur. Hence, studies of the flow behavior of human blood cells in models of à vessel obstruction and a sudden expansion of a vessel lumen were carried out. These showed that the particles were subjected to first high, and then much lower shear stresses as they entered the vortices where the environment appeared favorable for the formation of aggregates.The effects of high and variable shear stress on the release reaction and aggregation of platelets were therefore studied using cells labeled with C14-Serotonin suspended in Tyrodes-albumin undergoing oscillatory tube flow for 20 min at 37° C. There was no significant release of serotonin due to flow alone, but the thrombin-induced release of C14-activity was appreciably greater in suspensions subjected to shear rates > 2000 sec-1 than in control suspensions which had been incubated at rest. The synergistic effects of the shear flow were also noted in the presence of adrenaline, which increased the release reaction, and when [Ca++] was raised above the physiological level or acetyl salicylic acid added, which inhibited the release of serotonin.